High-Throughput Sequencing (HTS) of newly synthetized RNAs enables one shot detection and identification of live mycoplasmas and differentiation from inert nucleic acids. (May 2020) - Desbrousses, Céline; Archer, Fabienne; Colin, Adélie; Bobet-Erny, Alexandra; Champavère, Angélique; Gros, Edwige; Beurdeley, Pascale; Cruveiller, Stéphane; Tardy, Florence; Eloit, Marc
Abstract: Mycoplasma contamination threatens both the safety of biologics produced in cell substrates as well as the quality of scientific results based on cell-culture observations. Methods currently used to detect contamination of cells include culture, enzymatic activity, immunofluorescence and PCR but suffer from some limitations. High throughput sequencing (HTS) can be used to identify microbes like mycoplasmas in biologics since it enables an unbiased approach to detection without the need to design specific primers to pre-amplify target sequences but it does not enable the confirmation of microbial infection since this could reflect carryover of inert sequences. In order to unambiguously differentiate the presence of live or dead mycoplasmas in biological products, the present method was developed based on metabolic RNA labelling of newly synthetized mycoplasmal RNAs. HTS of labelled RNA detected A549 cell infection with Acholeplasma laidlawii in a manner similar to both PCR and culture and demonstrated that this technique can unambiguously identify bacterial species and differentiates infected cells from cells exposed to a high inoculum of heat-inactivated mycoplasmas. This method therefore combines the advantage of culture (that detects only live microorganisms) with those of molecular tests (rapidity) together with a very broad range of bacterial detection and identification.